Human embryonic hemopoiesis. Kinetics of progenitors and precursors underlying the yolk sac----liver transition. - Migliaccio, G (1986)
Human embryonic development involves transition from yolk sac (YS) to liver (L) hemopoiesis. We report the identification of pluripotent, erythroid, and granulo-macrophage progenitors in YS, L, and blood from human embryos. Furthermore, comprehensive studies are presented on the number of hemopoietic progenitors and precursors, as well as of other cell types, in YS, L, and blood at precisely sequential stages in embryos and early fetuses (i.e., at 4.5-8 wk and 9-10 wk postconception, respectively). Our results provide circumstantial support to a monoclonal hypothesis for human embryonic hemopoiesis, based on migration of stem and early progenitor cells from a generation site (YS) to a colonization site (L) via circulating blood. The YS----L transition is associated with development of the differentiation program in proliferating stem cells: their erythroid progeny shows, therefore, parallel switches of multiple parameters, e.g., morphology (megaloblasts----macrocytes) and globin expression (zeta----alpha, epsilon----gamma).